2015
DOI: 10.1002/anie.201501195
|View full text |Cite
|
Sign up to set email alerts
|

A Metal‐Free N‐Annulated Thienocyclopentaperylene Dye: Power Conversion Efficiency of 12 % for Dye‐Sensitized Solar Cells

Abstract: Reported are two highly efficient metal-free perylene dyes featuring N-annulated thienobenzoperylene (NTBP) and N-annulated thienocyclopentaperylene (NTCP), which are coplanar polycyclic aromatic hydrocarbons. Without the use of any coadsorbate, the metal-free organic dye derived from the NTCP segment was used for a dye-sensitized solar cell which attained a power conversion efficiency of 12% under an irradiance of 100 mW cm(-2), simulated air mass global (AM1.5G) sunlight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
104
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(111 citation statements)
references
References 71 publications
(25 reference statements)
7
104
0
Order By: Relevance
“…[10] Moreover, we observed that the presence of unreacted PBA in the crude affected the solubility of the final compounds. In fact, the addition of a small amount of PBA to a PBI solution caused precipitation of the latter, especially for those bearing amino acid groups (9)(10)(11)(12). This experimental evidence confirmed the hypothesis that traces of the perylene anhydride in solution facilitate the aggregation of the PBIs.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…[10] Moreover, we observed that the presence of unreacted PBA in the crude affected the solubility of the final compounds. In fact, the addition of a small amount of PBA to a PBI solution caused precipitation of the latter, especially for those bearing amino acid groups (9)(10)(11)(12). This experimental evidence confirmed the hypothesis that traces of the perylene anhydride in solution facilitate the aggregation of the PBIs.…”
Section: Resultssupporting
confidence: 67%
“…[11] This study highlights that the main factors influencing the reactions were the steric hindrance and the polarity of amines. [12] In the experiments, the steric bulkiness at the α-carbon influenced the outcome of the reaction. Amines with a small linear structure (1-6, 12-17) gave higher yields in shorter time.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19] The improvements of PCE were usually associated with a decrease in V loss to some extent. [20][21][22][23][24][25][26][27][28][29] However, a targeted down-regulation of V loss , which simultaneously reduces the V loss involved in electron injection, dye regeneration and interfacial recombination processes, is scarcely reported. Here, we report a comprehensive control of V loss in DSSCs through judicious molecular engineering of the sensitizer and the redox mediator.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Indeed, these organic sensitizers have demonstrated excellent light-harvesting ability and power-conversion efficiency (PCEs) of more than 12%. [6][7][8] Until now, the most widely used donor groups for DSSCs are based on triphenylamine and its derivatives, due to their for the first time as anchoring and acceptor group for DSSCs. And for comparison, the reference dye CA-4 with traditional cyanoacrylic acid anchoring group was also synthesized.…”
Section: Introductionmentioning
confidence: 99%